Systematic Literature Review on the Effectiveness of Wayground Interactive Learning Media in Mathematics Learning - I Made Edy Bangkit Saputra; Ketut Agustini; I Gde Wawan Sudatha (Cetta: Jurnal Ilmu Pendidikan, 2026)
The development of information technology has encouraged the adoption of interactive digital learning media to overcome the challenges of abstract mathematics learning and make it more concrete. This study aims to analyze the effectiveness of the Wayground platform (formerly Quizizz) as an interactive presentation medium in improving mathematics learning at the junior high school level. The research method used is a Systematic Literature Review (SLR) with the PRISMA model on 12 selected articles from 2021 to 2025. The articles discuss the effectiveness of learning media, particularly interactive or technology-based media, in the context of mathematics learning. The specific types of media include relevant interactive learning media, whether directly mentioning "Wayground" or similar types of interactive media aimed at improving mathematical concept understanding. The research design includes empirical studies such as development research, experiments, and classroom action research (CAR) that focus on learning outcomes and qualitative studies that discuss in depth the effectiveness of interactive learning media. The synthesis results show that, (1) Wayground features such as digital quizzes, flashcards, interactive discussions, real-time evaluations, and Paper Mode significantly support the creation of interactive and easily managed learning, (2) The application of Wayground has been proven to increase student motivation, engagement, active participation, and conceptual understanding in mathematics learning, (3) Interactive learning media such as Wayground effectively bridges the abstract nature of mathematics through visual and concrete presentation of concepts and enjoyable learning experiences, thereby improving learning outcomes. The implications of this study recommend the integration of Wayground into lesson planning and teacher training to optimize its features in order to create more effective and adaptive mathematics learning.